AUTOMATIC POSITIONING OF IMAGING PLANE IN ULTRASONIC IMAGING (2011)
The invention is directed to a method for ultrasonic imaging, in which two-dimensional images are acquired, one of which is aligned with a longitudinal direction of an interventional object (e.g. a needle) to be moved towards a target area within a subject of examination and the other one is intersecting the longitudinal direction of the interventional object and automatically positioned dependent on the automatically determined position and orientation of the interventional object. Further, the invention is directed to an ultrasonic imaging device adapted to conduct such a method.